Fermented Soy and Fish Protein Dietary Sources Shape Ileal and Colonic Microbiota, Improving Nutrient Digestibility and Host Health in a Piglet Model - Li, Ying; Han, Yunsheng; Zhao, Qingyu; Tang, Chaohua; Zhang, Junmin; Qin, Yuchang (Frontiers in Microbiology, 2022)
Suitable protein sources are essential requirements for piglet growth and health. Intestinal microbiota co-develops with the host and impact its physiology, which make it more plastic to dietary protein sources at early stages. However, the effects of fermented soybean meal (FSB) and fish meal (FM) on foregut and hindgut microbiota, and their relationship with nutrient digestion and host health remain unclear. In this study, we identified interactions between ileac and colonic microbiota which were reshaped by FSB and FM, and assessed host digestibility and host health in a piglet model. Eighteen weaned piglets (mean weight = 8.58 kg ± 0.44 kg) were divided into three dietary treatments, with six replicates/treatment. The level of dietary protein was 16%, with FSB, FM, and a mixture of fermented soybean meal and fish meal (MFSM) applied as protein sources. During days 1–14 and 1–28, diets containing MFSM and FSB generated higher piglet body weight (BW) and average daily gain (ADG), but lower feed to weight gain ratios when compared with the FM diet (P < 0.05). Piglets in the MFSM group had lower apparent total tract digestibility (ATTD) of crude protein (CP) and lower ATTD of ether extract (EE) when compared with FSB and FM groups (P < 0.05). Serum immunoglobulins (IgA, IgM or IgG) in MFSM and FM groups were significantly higher on days 14 and 28, but serum cytokines (interleukin-ILβ (IL-1β), IL-6, or tumor necrosis factor-α (TNF-α)) were significantly lower than the FSB group (P < 0.05). When compared with FSB and FM groups, dietary MFSM significantly increased colonic acetic acid, propionic acid, and butyric acid levels (P < 0.05). Piglets fed FSB had higher α-diversity in colonic microbiota (P < 0.05). Dietary FSB improved CP digestibility by increasing the relative abundance of ileac f_Lactobacillaceae and Lactobacillus, while dietary MFSM benefited TC digestibility by increasing f_Peptostreptococcaceae and Romboutsia. Dietary MFSM and FM enhanced immunoglobulin secretion by increasing colonic f_Streptococcaceae and Streptococcus prevalence, while dietary FSB promoted cytokine production by increasing microbiota diversity and Romboutsia and Christensenellaceae. Our data provide a theoretical dietary basis for young animals using plant and animal protein sources.